"Close–open–close free-flap technique" for the cover of severely injured limbs. (December 2019) - Bumbaširević, Marko; Palibrk, Tomislav; Georgescu, Alexandru Valentin; Soucacos, Panayotis; Matei, Ileana Rodica; Vučetić, Čedomir; Manojlović, Radovan; Marković, Dragan; Tos, Pierluigi; Nikolić, Slobodan; Glišović Jovanović, Ivana; Petrović, Aleksandra; et al.
Abstract: The treatment of severely injured extremities still presents a very difficult task for trauma orthopaedic surgeons. Despite improvements in technology and surgical/microsurgical techniques, sometimes a limb must be amputated, otherwise severe and potentially fatal complications may develop. There is a well-established belief that severe open fractures should be left open. However, Godina proved wound coverage in the first 72 h (after an injury) to be safe and to bring good final results. So early wound cover (no later than one week after an injury) with well vascularized free flaps became the gold standard. Yet for many patients (some of whom have serious health problems), operative treatment needs to be postponed when they arrive to specialized microsurgical departments for microsurgical reconstruction much later than one week after incurring an injury.  As the definite wound cover period from one week to 3 months seems to be hazardous, especially due to the potential of infection, we developed a safe, original flap technique that prevents infection and covers important structures such as exposed bones, tendons, nerves and vessels. We named this technique the "close–open–close free flap technique". It enables difficult wound cover in any biological phase of the wound, by combining complete flap cover first, with the removal of stitches from one side of the flap after 6–12 h. This technique works very well for borderline cases as well; where even after a complete debridement, dead tissue still remains in the wound - making wound cover very dangerous. Closing completely severe open fractures with free (or pedicled) flaps and removing the stitches on one side after 6–12 h, enables orthopaedic surgeons to safely cover any kind of wound in any biological phase of the wound. Additional debridements, lavages and reconstructions can easily be performed under the flap and after the danger of a serious infection has disappeared, definitive wound closure can be carried out.